FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN AUDITOR OLEH KLIEN - Dwi Satriyo Adi Nugroho; Imam Ghozali (Diponegoro Journal of Accounting, 2015)
Period of audit tenure between auditor and its client companies have an impact to auditor independency. Therefore companies obliged to make change or rotation of auditor. This is in accordance with Financial Minister Statutory No.423/KMK.06/2002, determine limitation of audit tenure, then it has impact to audit firm switching.This research aims to determine the factors that influence the changes of the auditor by the client.            The Data being used is from manufacturing company which is listed in “Bursa Efek Indonesia” (BEI) in 2010-2012 period. Variabel used in this research are management change, auditor’s reputation, financial distress, company growth, audit opinion, accounting firm size, and auditor changes. By using logistic regression in SPSS 19 software, this research tried to test the effect of management switching, auditor’s reputation,  financial distress, company growth, audit opinion, and accounting firm size toward auditor changes.            The result of this research shown below : (1) management change has no effect towards auditor changes, (2) auditor’s reputation has no effect towards auditor changes, (3) financial distress has no effect towards auditor changes, (4) company growth has positive effect towards auditor changes, (5) audit opinion can’t be analyzed because data audit opinion companies obtained an unqualified opinion on the financial statements during the period of research, (6)accounting firm size can’t be analyzed because in the research period data is worth constant so it can not be processed.